Bioavailability in Rats of Human Recombinant Tissue Plasminogen Activator After Subcutaneous and Intramuscular Injection - Garcia Frade, L J; Poole, S; Hanley, S; Creighton, L J; Curtis, A D; Gaffney, P J (Thrombosis and Haemostasis, 1986)
The bioavailability of human recombinant tissue plasminogen activator (rt-PA) in rats was measured after subcutaneous (s.c.) and intramuscular (i.m.) injection. Rt-PA was absorbed after both i.m. and s.c. injection, giving peak plasma concentrations within 30 min and 1 h, respectively, with detectable concentrations up to 6 h. These peak values of bioavailable t-PA were obtained in a functional fibrin plate assay of euglobulin precipitates and expressed as +88% and +243% (for s.c. and i.m. routes respectively) above basal rat fibrinolytic activity. Prior injection of rt-PA, s.c. or i.m., significantly reduced the weights of thrombi induced in the inferior vena cava after injection.
Keywords: Recombinant tissue plasminogen activator; Subcutaneous; Intramuscular; Rat; Thrombus